(untitled) (Proceedings of International Educators Conference, 2023)
Emphasize is known to cause comprehension trouble, but experimental deciphering thinks about its particular effect has been scattered. Concurring with Mazzetti (1999), an emphasis is composed on digressed phonemics and prosody, both talked about broadly within the TESL teach. The current study seeks to look at, within the translating setting, the pertinence of Anderson-Hsieh, Johnson, and Koehler’s (1992) finding that veering off prosody ruins comprehension more than tricky phonemics and syllable structure do. Thirty-seven graduate-level translating majors, doled out arbitrarily to four bunches, rendered four adaptations of a text perused by the same speaker and after that filled out a survey whereas playing back their possess versions.